Harnessing the preconditioning phenomenon: does remote organ ischaemia provide the answer?. Issue 10 (13th September 2005) - Burdess, A; Newby, D
Abstract : Despite progress in defining the cellular mechanisms of the ischaemic preconditioning phenomenon, its conversion into convenient clinical practice has been slow. The possibility that an innate mechanism of tissue resistance to ischaemia could be harnessed as a clinical tool is an attractive and enticing prospect